Navigating language barriers: Hebrew proficiency and self-efficacy among Muslim Arab Bedouin students in Israeli higher education - Abu-Rabiah, Eihab (Journal of International Students, 2025)
This study examines the Hebrew language proficiency of Muslim Arab Bedouin students in Israeli higher education, focusing on the four language skills—reading, writing, listening, and speaking—and self-efficacy levels. Using quantitative methods, including standardized language tests and self-efficacy questionnaires, data were collected from thirty-seven students. Results indicate no statistically significant differences in proficiency across the four skills, though female students outperformed males in writing. Writing also showed the strongest correlation with overall language proficiency. Notably, strong correlations were found between reading and speaking, whereas listening exhibited weaker associations with other skills. Self-efficacy levels were higher for productive skills (speaking and writing) than for receptive skills (listening and reading), with reading showing the lowest self-efficacy.